Disrupting the disruptive: making sense of app blocking in Brazil - Jacqueline de Souza Abreu (Internet Policy Review)
Brazil has a record of judicial orders demanding that intermediaries such as local internet access providers and app stores administrators “block” user access to social media applications (such as YouTube, Facebook, Secret, and WhatsApp), because the application allegedly either provides an illegal service or has failed to comply with a court order. This paper reflects on this phenomenon and adds to a body of literature that tries to understand why internet blocking practices are enacted by looking at the context in which they happen. Upon review of episodes of social media blocking in Brazil, it argues that the blocking orders issued by Brazilian judges can be connected with a scenario of “regulatory disruption”, that is, a context of regulatory frameworks unfit to deal with innovative internet applications. This context expands the role of the judiciary in resolving legal disputes. Given that this disruptive scenario is not per se exclusive to Brazil, the paper suggests that the practice is further associated with the country’s legal culture, judicial behaviour, and level of social and institutional development.